MODEL OPTIMASI PENJADWALAN PRODUKSI FLOWSHOP DENGAN WAKTU PROSES DINAMIS - Joko Sulistio (Teknoin, 2015)
In a mass production system, work stationsare designed base on the production process flow. This layout is called flowshop. The advantage of flowshoplays on it simple material flow. Therefore, the material transportation time can be minimized and the total production time is shortened respectively. Generally, flowshop scheduling applies Johnson algorithm, Campbell, Dudek and Smith (CDS). Nevertheless, those algorithms are just an approach. Therefore it can’t provide an optimal solution. This article explain the flexible flowshop scheduling with Mixed Integer Programming (MIP). Every parts type scheduled will not enter the same work station and some work station are served manually by an operator that leads to a dynamics process time. Simulation is applied to estimate the process time in those work station. A case study is utilize for this purpose. The makespan of the proposed model exhibits a 14 minutes shorter that the initial time.